Are our data ready for the next global challenges? Resilient data for resilient societies and economies. Issue 138 (December 2022) - Schaepman, Michael; Tarantino, Matteo; Aggarwal-Khan, Sheila; Biller-Andorno, Nikola; de Giorgi, Giacomo; Ducrest, Jacques; Messerli, Peter; Phakeng, Mamokgeti; Türk, Volker; Stoffel, Markus
Highlights: COVID-19 has shaken a wide range of national systems and infrastructures, including health, welfare, environment or security. The related challenges cannot be tackled in isolation as all parts of the systems are tightly interlocked and interdependent. Addressing scenarios emerging from these interlocking challenges require transversal approaches and agile public policies. Yet, approaches and policies depend on a steady, continuous supply of reliable data from a suite of domains and disciplines.